Binding of fluorescent dansyl amino acids in albumin: When access to the protein cavity is more important than the strength of binding - Bertozo, Luiza de Carvalho [UNESP]; Maszota-Zieleniak, Martyna; Bolean, Maytê; Ciancaglini, Pietro; Samsonov, Sergey A.; Ximenes, Valdecir F. [UNESP] (Elsevier, 2021)
Human serum albumin (HSA) is the primary drug carrier protein in the blood plasma. To perform this task, it has two cavities (sites I and II) where the pharmaceutical drugs can be bound. Dansyl amino acids are fluorescent markers widely used to identify the binding sites of new drugs. Here, we found intriguing differences between site I and site II for dansyl amino acids. These findings might open new perspectives for the studies of the interaction of drugs with albumin. In a comprehensive experimental and theoretical approach, six dansyl amino acids that are supposed to be specifically bound either to site I or site II were characterized. The interactions were evaluated by fluorescence quantum yield, fluorescence lifetime, anisotropy, association constant, induced circular dichroism, and isothermal titration calorimetry. All these techniques showed that dansyl amino acids of site II are significantly better ligands compared to the ones of site I. Oppositely, the binding free energies obtained by the molecular dynamics-based approaches suggested that dansyl amino acids bind stronger to site I. These results, contradictory at first glance, were clarified by calculating the Potential of Mean Force corresponding to ligand unbinding. These data suggested that the ligands could easier access site II than site I, explaining the experimental data. In conclusion, the access of a potential ligand of albumin to its binding site might be crucial for their interactions and in the design of new practical applicability as a drug-albumin.
Keywords: Albumin binding sites; Dansyl amino acids; Fluorescence; Human serum albumin; Isothermal titration calorimetry; Molecular modeling